Spatial Pattern and Distribution of Adansonia Species in the Sahel Savanna Ecosystem of Yobe State, Nigeria - Ishaya Yahaya Kuku; Edicha Jibril Abdullahi; Bitrus Eniyekenimi Daukere; Jedidiah Precious Oru-Bo (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
Adansonia species, particularly baobab, are ecologically and socioeconomically significant in the Sahel Savanna, yet their spatialdistribution patterns remain underexplored in Nigeria. This study employed a reconnaissance survey to delineate the study area and inform the establishment of purposively selected quadrats ranging from 100 x 100 m to 500 x 500 m, based on local Adansonia density and distribution. All individual trees were identified and measured for structural attributes, with their geographic coordinates collected using calibrated GPS devices and validated through multiple readings and inter-observer checks. Nearest Neighbour Analysis (NNA) in ArcGIS 10.8 was used to analyze the spatial patterns by comparing observed mean distances to expected values under random distribution. Results revealed that Adansonia species, predominantly A. digitata and A. kilima, exhibited a dispersed distribution pattern across 19 of 20 quadrats, with only one quadrat showing randomness. This pattern suggests influences from resource competition, seed dispersal strategies, environmental heterogeneity, and human management. The study provides critical insights for conservation planning and sustainable management of baobab in arid environments.